Comparative study between open and laparoscopic lymphadenectomy (pelvic and para-aortic) in gynecological malignancies - Yassin, Hytham R.; ALShakhs, Soliman; Hamed, Mohammed; Karam, Adel; Mouneer, Mohammed (International Surgery Journal, 2018)
Background: Objective of present study was to compare the results of lymphaenectomy (pelvic and para-aortic) between laparoscopy and laparotomy in gynecological malignancies. Methods: Authors analyze the results of 30 patients suffering from gynecological malignancies (Enometrial, Ovarian and cervical) submitted to surgery as apart of treatment. Patients were classified in Two Groups Group (1) included15 patients were submitted to open radical surgery and group (2) included 15 patients Were submitted to laparoscopic radical surgery between May 2016 and October 2017. Results: In present comparative study, there was significant difference regarding intra operative blood loss, operative time and post operative hospital stay (P<0.001) and there was no significant difference regarding intra-operative complications, post-operative complications, total number of lymph node harvested, number of positive lymphnodes (P>0.05). Conclusions: Laparoscopic lymphadenectomy is a technically feasible and safe procedure. Authors recommend further study in large number of patients with longer duration and follow up period for assessment of oncological out-come.